The Effects of Slavery on Enslaved People and Eighteenth-Century Antislavery Arguments - Julia Jorati (Journal of Modern Philosophy)
Many antislavery authors in the eighteenth century contend that enslavement degrades the human mind and causes enslaved people to exhibit inferior moral or intellectual traits. They often use this contention to combat the racist claim that Black people are naturally inferior to Whites and that this natural inferiority justifies enslavement, insisting instead that the disparity is simply an effect of enslavement. After examining this argumentative strategy and what makes it appealing, this paper investigates several ways in which it is problematic. First, this strategy was sometimes used to oppose the immediate abolition of slavery: some eighteenth-century authors argue that many enslaved people have become incapable of living good lives outside of slavery and that immediate emancipation would therefore be detrimental for them and for society. Moreover, this strategy may further marginalize and demonize an already oppressed group and it sometimes blames, or seems to blame, enslaved people for their condition. The paper ends with some reflections on whether the strategy can nevertheless be useful for antislavery purposes.